The coronavirus conundrum - BA.2.86 variant of SARS-CoV-2 – What’s new about long COVID – Vaccines - Nobel Prizes - Romero, José Pacheco (2023)
The coronavirus has continued to move around the world with new variants, someof which are of concern. Hospitalizations increased in some places with the BA.2.86variant, especially in obese or morbid elderly people, but have decreased, as havedeaths. Women who gestated by assisted reproductive techniques had similarmorbidity as those who gestated spontaneously, but with more adverse maternalperinataloutcomes in those older, with multiple pregnancies, nulliparity, body massindex >30. Children born at the beginning of the pandemic showed a differentmicrobiome composition than those born before the pandemic, which could affecttheir health later in life. Among people with long COVID, a quarter of them sufferorgan and system sequelae, with limitation and lost years of activity, as well asthe possibility of premature death. Long COVID occurs more in women between35-49 years of age and in those with lower income. They could develop type 2diabetes. There would be direct interactions between SARS-CoV-2 and mitochondrialproteins essential in energy production. Viral RNA has been detected in coronaryatherosclerotic lesions and the spike has been found in skull bones, meninges andbrain. Coronavirus vaccines protect pregnant women and their newborns throughplacental transfer and lactation. In the population, protective immunity frominfection and vaccines declines over time and new vaccination will be required at anas yet undetermined regularity.